2011
DOI: 10.1007/s11682-011-9121-8
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging in Huntington’s disease reveals distinct patterns of white matter degeneration associated with motor and cognitive deficits

Abstract: White matter (WM) degeneration is an important feature of Huntington's disease (HD) neuropathology. To investigate WM degeneration we used Diffusion Tensor Imaging and Tract-Based Spatial Statistics to compare Fractional Anisotropy, Mean Diffusivity (MD), parallel diffusivity and perpendicular diffusivity (λ⊥) in WM throughout the whole brain in 17 clinically diagnosed HD patients and 16 matched controls. Significant WM diffusivity abnormalities were identified primarily in the corpus callosum (CC) and externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
60
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 49 publications
8
60
2
Order By: Relevance
“…In the present paper, independent of age, we found a weak connection between high CAG repeat length and brain abnormality: high CAG repeats correlated with high connectivity impairment. This genetic basis for WM alterations was not found in two previous diffusion CC studies (Rosas et al 2010;Bohanna, Georgiou-Karistianis, Sritharan et al 2011), where CAG repeat length did not correlate with diffusivity measures. This may have to do with the increased sensitivity of tractography to elucidate the microstructural changes in WM or variations in subjects' demographics.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…In the present paper, independent of age, we found a weak connection between high CAG repeat length and brain abnormality: high CAG repeats correlated with high connectivity impairment. This genetic basis for WM alterations was not found in two previous diffusion CC studies (Rosas et al 2010;Bohanna, Georgiou-Karistianis, Sritharan et al 2011), where CAG repeat length did not correlate with diffusivity measures. This may have to do with the increased sensitivity of tractography to elucidate the microstructural changes in WM or variations in subjects' demographics.…”
Section: Discussioncontrasting
confidence: 50%
“…Nevertheless, these previous macro-and microstructural studies focused on wholebrain WM or Region of Interest analyses. Only a few studies investigated a specific tract in its entirety, for example, the whole commissural fiber (Magnotta et al 2009;Muller et al 2011;Di Paola et al 2012;Dumas et al 2012), the motor corticostriatal circuit (Kloppel et al 2008;Bohanna, Georgiou-Karistianis, Sritharan et al 2011) or the WM pathway of the sensorimotor cortex (Dumas et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In line with our finding, diffusion tensor imaging studies have shown structural disconnecitivty in symp-HD individuals in the motor-cortical projection region of putamen. 61 A PET study revealed a corticostriatal motor network that discriminated pre-HD individuals from controls. 15 A further PET study showed that altered excitation of the striatum can modulate widespread cortical networks.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Herein, by using TBSS, we present another common feature of ARSACS with these diseases: extensive WM alterations in the brain. 32,33 Our current study was distinguished in several ways: First, to the best of our knowledge, our study was the first that investigated whole-brain WM in patients with ARSACS. Second, it quantified the abnormal pattern of diffusion indices, including RD and AD, indicating widespread WM disintegration.…”
Section: Discussionmentioning
confidence: 99%